Hybrid natural fiber composites based on cashew apple bagasse and mahogany fruit for multifunctional performance - Nashmi H. Alrasheedi; P. Manoj Kumar; D. Balaji; M. Sathishkumar (Journal of Materials Research and Technology)
This study investigates the mechanical and acoustic properties of hybrid composites developed from Cashew Apple Bagasse (CAB) fibers and a Mahogany Tree Fruit Filler (MFF) reinforced with an epoxy matrix. In this study, the effect of NaOH treatment (5 % and 10 %) on CAB fibers at different MFF weight fractions (0–25 wt %) was studied. The results demonstrate that the composites treated with 5 % NaOH and had 15-20 wt% MFF showed the best results. It exhibited a 40 % increase in tensile strength, a 50 % increase in flexural strength, a 45.71 % increase in impact strength, and a 56.67 % increase in the noise reduction coefficient (NRC) compared to the untreated samples. These improvements can be attributed to the removal of surface impurities on the fiber surface, improved fiber-matrix bonding, and dispersion of the filler in the matrix. Using sodium hydroxide (NaOH) beyond the threshold value (10 %) with a high filler content (>20 wt %) made the fibers to break down and clump together, which decreased its mechanical and acoustic performance. The combination of CAB and MFF in a hybrid composite showed the best synergetic approach, striking a good balance between reinforcement and load transfer efficiency. These composites can be used in car interior, soundproof panels, and lightweight structures.